Mechanisms of Immunity in Typhus Infections IV. Failure of Chicken Embryo Cells in Culture to Restrict Growth of Antibody-Sensitized Rickettsia prowazeki - Wisseman, C. L. (1974)
Rickettsia prowazeki, pretreated with typhus immune human serum, readily infects, and grows in, chicken embryo cells in culture. This finding is similar to those of previous studies which showed that typhus rickettsiae, pretreated with immune serum, grow in cells of the yolk sac of embryonated hen eggs and in the cells of the midgut of the human body louse. In contrast, identically treated typhus rickettsiae were destroyed by human macrophages in culture. Collectively, these observations seem to support an emerging concept that the fate of antibody-sensitized typhus rickettsiae depends upon the presence or absence of certain specialized properties of the host cell into which they gain entrance—nonphagocytic cells or “nonprofessional” phagocytic cells versus certain kinds of “professional” phagocytes. The phenomena involved probably have an important bearing on the mechanisms of the persisting infection and the nonsterile immunity which characterizes convalescence from typhus fever in man. They also form the basis for certain practical technical innovations in the laboratory.